DAMPAK PENGELOLAAN BANGUNAN AIR DAS WAE PESSY TERHADAP KETERSEDIAAN AIR BERSIH MASYARAKAT NEGERI HUKURILA, KOTA AMBON - Wahdania Ashari; Bokiraiya Latuamury; Jan W. Hatulesila (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Clean water availability is a fundamental issue for coastal communities in Hukurila, South Leitimur, Ambon City, which currently face ecological degradation. This study aims to analyze the effectiveness of the Wae Pessi Watershed Water Structure through social, technical, and ecological approaches. A qualitative descriptive method with a case study approach was employed, involving observations, document reviews, and in-depth interviews with 30 respondents. Additionally, time-series regression was used to analyze water discharge data from the 2010–2015 period. The results indicate that the Wae Pessi Water Structure significantly increased economic benefits (t-ratio=6.86; p=0.0088) and decreased water-borne diseases (t-ratio=−6.90; p=0.007). Perceived positive impacts include a reduced domestic burden on women and children, improved commodity quality, and supported household production, backed by adequate water discharge (ranging from 1.2–4.1 m3/second). However, water distribution remains unequal between the upstream and downstream areas. The sustainability of this system relies heavily on integrating modern technology with local ecological wisdom